2021
DOI: 10.1177/2058460121990293
|View full text |Cite
|
Sign up to set email alerts
|

CT and MR imaging findings of bilateral ovarian metastasis from renal cell carcinoma: a case report

Abstract: Secondary ovarian involvement by renal cell carcinoma rarely occurs. Here, we describe the computed tomography and magnetic resonance imaging findings of bilateral ovarian metastases from renal cell carcinoma that demonstrated heterogeneous strong contrast enhancing tumors with flow voids around and within the tumors. In addition, the apparent diffusion coefficients of the malignant tumors were high. These findings were similar to those of renal cell carcinomas at primary and other metastatic sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…To the best of our knowledge, there are 28 previous publications with 39 cases, and the present case was the 40th case reported [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] . A summary of the cases is presented in Table 1 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…To the best of our knowledge, there are 28 previous publications with 39 cases, and the present case was the 40th case reported [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] . A summary of the cases is presented in Table 1 .…”
Section: Discussionmentioning
confidence: 91%
“… [1] reported that 0.2% of RCCs metastasized to the ovaries. Although there are 39 cases and some literature reviews about ovarian metastasis of RCC have been previously reported [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , to the best of our knowledge, no review has focused on the radiological features of ovarian metastasis of RCC. Herein, we reported a case of ovarian metastasis of RCC and a review of the literature demonstrating the radiological features of the tumor.…”
Section: Introductionmentioning
confidence: 99%